Zanzibar its history and its people - Ingrams, William Harold 1897- (Stacey International, 2007)
This classic text on Zanzibar makes available again the remarkably comprehensive account of the Island of Cloves, written by W. H. Ingrams and first published in 1931. Zanzibar, Its History and Its People is essentially an historical ethnography of Zanzibar. The author describes local legends, and their important social function in recording and constituting the oral history of the island. Ingrams' extensive observations and personal experiences - both on the main island of Unguja and Pemba and the smaller islands which make up Zanzibar - provide a detailed and lively account of society at the time and make engaging reading. Zanzibar, Its History and Its People is a comprehensive work, perhaps daunting on account of its size, but a joy to read and a rich resource.